E-Transparency in Providing Information Services Through Village Websites - Rofi'ah, Saifina Alfiyatur; Kumalasari, Ana; Lukita, Cahyo (Publik : (Jurnal Ilmu Administrasi), 2023)
Increasing e-transparency encourages village governments to provide information to the community through village websites. This research aims to provide an overview of e-transparency in providing information services through the village website. This research uses descriptive research with a case study approach. The research focuses on Kiknadze's theory, namely providing information through online media, offering online information to the public, and using e-platforms. Data collection was obtained through observation, interviews, and documentation. The research results show that Prambatan village website has quite complete features. However, providing information on the website is only limited to the activities carried out, while information such as village finances is not yet transparent enough, because the website manager has limitations in providing information that is considered private. However, in this case, the Village government has offered the community to participate in providing suggestions and input for the Village, but some residents still do not know about the existence of the website and are less active in providing suggestions and input. The village government has not fully implemented the Prambatan village website as an e-platform in decision-making. The Prambatan Village still uses the direct deliberation method.